2017
DOI: 10.3390/healthcare5010012
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and Trace Elements Intakes and Food Consumption Patterns of Young Children Living in Rural Areas of Tibet Autonomous Region, P.R. China: A Cross-Sectional Survey

Abstract: Background and objectives: Several studies revealed clinical signs of stunting and rickets among rural populations of Tibet Autonomous Region (T.A.R.), and especially amid children. Further, these populations are affected by a bone disease named Kashin-Beck disease (KBD). However, little is known about the dietary status of this population. This survey aimed to assess the usual intakes of young Tibetan children living in rural areas around Lhasa for energy, water, and ten minerals and trace elements (Na, K, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 72 publications
1
9
0
1
Order By: Relevance
“…A study by Wu et al [34] found that this short term elevation in BP returned to baseline levels within 3 months. High-sodium intake among Tibetans [35,36] also influences their BP levels. Urinary sodium and sodium to potassium ratio excretion was higher in Tibetans than in Han subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wu et al [34] found that this short term elevation in BP returned to baseline levels within 3 months. High-sodium intake among Tibetans [35,36] also influences their BP levels. Urinary sodium and sodium to potassium ratio excretion was higher in Tibetans than in Han subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of processing machines made from mild or galvanised iron metal, drying of pre-processed products by the road-side, and display of fully processed products in open containers at point of sale increases the possibility of product contamination either from metals or microorganisms (Bolade, 2016). Food products normally account for a high proportion of trace metal intake in adults and children (Dermience et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, congenital heart disease, hypertension, and other diseases have high morbidity in Tibet and may be influenced by the extreme living environments [24]. The plateau environment not only impacts the human body but also lifestyles, and thus may also affect PA. Several studies have reported on the growth and development characteristics of children and adolescents in Tibet [25,26], as well as the related situations of eye diseases [24], rickets/Kaschin-Beck disease [27,28], and nutrition [29,30,31]. However, no study has examined PA.…”
Section: Introductionmentioning
confidence: 99%